ANALISIS PENGARUH FAKTOR-FAKTOR PERILAKU TUGAS, PERILAKU HUBUNGAN, MOTIVASI INTRENSIK, MOTIVASI EKSTRENSIK, DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN BAGIAN PRODUKSI PT. MADUKARA MALANG - Sriwati Sriwati (Universitas Riau Kepulauan, 2015)
Problem formulation which can be laid open in this research shall be as follows: 1) Whether behavioral factors of leader, motivate and environment work by together have an effect on to labour capacity of employees on part of production at PT. Madukara Malang, 2) Among behavioral factors of leader, motivate and environment work the, which factor having an effect on dominant to labour capacity of employees on part of production at PT. Madukara Malang. As for research target is to analyze the behavioral factors influence of leader, motivate, and environment work by together to labour capacity of employees on part of production at PT. Madukara Malang and also to analyze which the factors among behavioral factor of leader, motivate, and job environment having an effect on dominant to labour capacity of employees on part of production at PT. Madukara. Result of test F indicate that by together behavioral variable of duty, behavioral of relation, motivate the intrinsic, motivate the extrinsic, and environment work by together have an effect on by significant to labour capacity of employees on part of production at PT. Madukara Worse luck, meaning progressively mount the duty behavioral, behavioral of relation, motivate the intrinsic, motivate the extrinsic, and environment work hence reached labour capacity will mount. Result of research indicate that the change of labour capacity equal to 78,2% because of change by together duty behavioral, behavioral of relation, motivate the intrinsic, motivate the extrinsic, and environment work, while the rest 21,8% because dissimilar variable which not checked. Result of t test obtained by result that duty behavioral, behavioral of relation, motivate the extrinsic and environment work to have an effect on by significant to labour capacity. In the reality behavioral variable of duty represent the dominant variable have an effect on to labour capacity, become the head behavioral represent the variable having an effect on dominant to labour capacity of employees on part of production PT. Madukara worse luck tested.